Control of hypertension in Italy: results of the "Study on Antihypertensive Treatment in General Practice (STAP)". Physicians Taking Part in STAP - Avanzini, F; Alli, C; Colombo, P; Corsetti, A; Colombo, F; Tognoni, G (Giornale italiano di cardiologia, 1998)
Various epidemiological surveys from different countries have documented the unsatisfactory control of arterial hypertension. The aim of this study was to assess the current status of treatment and control of hypertension in Italy. A random sample of general practitioners (GP) working in several Aziende Sanitarie Locali (Local health offices-ASL) throughout Italy were invited to take part in the study. Each doctor had to recruit a random sample of 15-20 hypertensive patients receiving antihypertensive drugs among those attending his/her office for any reason. A standard medical history, specifically oriented to hypertension and its pharmacological treatment, was taken for each patient. Three blood pressure (BP) measurements were made, with the patient seated for at least 5 minutes, using an accurate automatic device (A&D UA-732), and the mean was taken as each patient's BP. A total of 73 GPs (17% of the invited sample), working in 14 Italian ASL (six in the north of the country, four in the center and four in the south and islands), agreed to participate in the study. They recruited an average of 17 patients each, for a total of 1204 hypertensive subjects (663 women and 541 men) 633 of whom were 65 years old or more, mean age 64 +/- 11 years, range 25-94 years. More than half (56%) had been taking antihypertensive drugs for at least five years; 42% were taking one drug, 40% two, 16% three and 2% four drugs. Respectively, 63% and 23% had systolic BP (SBP) > or = 140 and > or = 160 mmHg; 28% and 14% had diastolic BP (DBP) > or = 90 and 95 mmHg. In 71%, BP was < 160/95 mmHg, but only 33% had BP lower than 140/90 mmHg. BP control was similar in males and females, but worse in the elderly. Nine percent of patients complained of symptomatic side effects, usually mild. Only 8% admitted to poor compliance with the antihypertensive therapy, and their BP was significantly less well controlled. Control of BP in patients receiving antihypertensive drugs is still far from optimal in Italy, just as in other countries. This situation seems more related to the fact that doctors do not tackle the problem aggressively, than to the patients' degree of compliance with therapy.